Probation and parole case management as opportunity-reduction supervision. Issue 7 (3rd October 2017) - Schaefer, Lacey; Williamson, Harley
ABSTRACT: Recent developments in probation and parole show a shift from the traditional control and treatment approach towards opportunity-reduction supervision strategies. Studies show that although opportunity-reduction supervision is not yet an organizing framework for practice, many practitioners rely on these tactics informally as an approach to case management. The current study uses survey data to explore the predictors of surveillance, rehabilitation, and opportunity-reduction strategies used by probation and parole officers. Results indicate job burnout and stress are the strongest predictors of the supervision strategies that officers use. Implications for the use of opportunity-reduction supervision strategies in offender case management are discussed.